1999
DOI: 10.1002/1531-8249(199911)46:5<791::aid-ana18>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging in spontaneous attacks of SUNCT: Short-lasting neuralgiform headache with conjunctival injection and tearing

Abstract: A 71‐year‐old woman presented with a short history of episodes of severe left‐sided orbital and temporal pain in paroxysms lasting 60 to 90 seconds, and accompanied by ipsilateral lacrimation of the eye, rhinorrhea, and conjunctival injection. Results of clinical examination and structural imaging were normal and a clinical diagnosis of SUNCT (short‐lasting unilateral neuralgiform pains with conjunctival injection and tearing) was made. The patient had a BOLD contrast–magnetic resonance imaging study in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
227
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(241 citation statements)
references
References 16 publications
8
227
0
5
Order By: Relevance
“…In view of the functional imaging evidence of activation of the posterior hypothalamus region being linked to attacks of SUNCT [5] and the broad experience in the use of posterior hypothalamic region deep brain stimulation (DBS) in patient with medically intractable cluster headache (CH), three patients with intractable SUNCT have been treated with DBS in the region of the posterior hypothalamus. The outcome of the three patients was promising, with a significant and sustained decrease in attack frequency, respectively, at 18-month [37], 12-month [38] and 15-month follow-up [39].…”
Section: Deep Brain Stimulation Of the Posterior Hypothalamic Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the functional imaging evidence of activation of the posterior hypothalamus region being linked to attacks of SUNCT [5] and the broad experience in the use of posterior hypothalamic region deep brain stimulation (DBS) in patient with medically intractable cluster headache (CH), three patients with intractable SUNCT have been treated with DBS in the region of the posterior hypothalamus. The outcome of the three patients was promising, with a significant and sustained decrease in attack frequency, respectively, at 18-month [37], 12-month [38] and 15-month follow-up [39].…”
Section: Deep Brain Stimulation Of the Posterior Hypothalamic Regionmentioning
confidence: 99%
“…The activation of the posterior hypothalamus during attacks, demonstrated in functional neuroimaging studies [5,6], has led to the hypothesis that the posterior hypothalamus plays a crucial role in the pathophysiology of SUNCT syndrome. However, besides the occurrence of ipsilateral autonomic symptoms during attacks, there are few other similarities shared between SUNCT/SUNA and the other TACs syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…No SUNCT foi descrita uma ativação da área postero-inferior do hipotálamo ipsilateral a dor 19 , mesma alteração encontrada na cefaléia em salvas 20 , bem como uma ativação hipotalâmica bilateral 21 . Esses achados falam a favor de uma origem central para esta cefaléia.…”
Section: Discussionunclassified
“…11 This latter area was initially thought to be activated only in cluster headache, and was proposed as the cluster generator. 11 It was subsequently shown, however, that this hypothalamic area is also activated during SUNCT, 12 PH, 13 and hemicrania continua. 14 Hemicrania continua is a strictly unilateral headache accompanied by ipsilateral oculofacial autonomic symptoms not now considered to be a trigeminal autonomic cephalalgia, because of its long-lasting pain.…”
Section: Rationale For Hypothalamic Stimulation In Headachementioning
confidence: 99%
“…63 After a functional MRI study had shown increased blood flow in the ipsilateral posterior inferior hypothalamus during SUNCT attacks, 12 the posterior inferior hypothalamus of a patient experiencing severe intractable SUNCT was implanted. 64 Prolonged stimulation resulted in long-lasting pain relief without continuous drug administration and with virtually no adverse effects.…”
Section: Sunct Syndrome and Paroxysmal Hemicraniamentioning
confidence: 99%